Cellular differentiation and gentic aspects of the trypanosome life cycle. - Kooy, R.F. (Utrecht University, 1991)
This collection of papers (submitted as a doctoral thesis) considers the various aspects of cellular differentiation and genetics of the trypanosome life cycle. The first chapters gives a general introduction to African trypanosomiasis. The next 4 discuss the DNA content of the genus Trypanosoma, identification of a facultative haploid life cycle stage in African trypanosomes, cell cycle synchronization of Trypanosoma brucei cultured in vitro, with aphidicolin measured by flow cytometry, and the karyotypes and comparative DNA contents of parental and hybrid T. brucei. Several of the sections in the book have been, or will be published elsewhere and are multi-authored.